2021
DOI: 10.1148/rycan.2021200157
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomic Analysis of Locally Advanced Lung Cancer Based on CT Imaging and Intratreatment Changes in Cell-Free DNA

Abstract: L ocally advanced, inoperable lung cancer is a challenging disease. Despite aggressive treatment with chemoradiation, local cancer recurrence is observed in approximately 50% of patients (1), and the median survival rate is only 23 to 25 months (2). Imaging genomics, otherwise known as radiogenomics, is a promising technique which can potentially improve prognostication and help guide new treatment strategies. This emerging field aims to capture the molecular subtypes and genetic underpinnings of a disease bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Aerts et al, investigated the prognostic value of tumor phenotypes defined by radiomics for both lung cancer and head-and-neck cancer [ 17 ]. Lafata et al, analyzed the association of radiomics features with underlying tumor mutational and cfDNA patterns [ 18 ] and performed first associations with p53 status, however, only focused on primary lung tumors and not on multiple metastases. A recently published study by Starmans et al, demonstrated that radiomics and machine learning features from CT can predict histopathological tumor growth patterns in colorectal liver metastases [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aerts et al, investigated the prognostic value of tumor phenotypes defined by radiomics for both lung cancer and head-and-neck cancer [ 17 ]. Lafata et al, analyzed the association of radiomics features with underlying tumor mutational and cfDNA patterns [ 18 ] and performed first associations with p53 status, however, only focused on primary lung tumors and not on multiple metastases. A recently published study by Starmans et al, demonstrated that radiomics and machine learning features from CT can predict histopathological tumor growth patterns in colorectal liver metastases [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies choose many different ways to focus on lung cancer. In one study [ 31 ], only late-stage patients were included. Two studies [ 29 , 51 ] only included early-stage lung cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included different subtypes of lung cancer, and small cell lung cancer was typically excluded. Only two studies allowed small cell lung cancer [ 31 , 33 ], though one [ 33 ] only had 3% cases with this subtype. One study focused on adenocarcinomas [ 51 ] and one focused on squamous cell carcinomas [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, radiomic analysis facilitates characterization of complex radiogenomic interactions that can be used to study basic biology and identify prognostic markers during treatment [ 38 , 39 ]. Agnostic features have been shown to add complementary insight compared to conventional semantic features, including disease staging and tumor volume [ 40 ].…”
Section: Discussionmentioning
confidence: 99%